PATA Youth Symposium 2018 & PATA Travel Mart 2018 / Mohd Faisal Abdul Wahab and Zarifah Mohd Zain - Abdul Wahab, Mohd Faisal; Mohd Zain, Zarifah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
UiTM Cawangan Pulau Pinang was invited to send a group of delegates as participants and volunteers at PATA Youth Symposium (PYS) 2018 and PATA Travel Mart (PTM) 2018 respectively. It was an honor for UiTM Cawangan Pulau Pinang to be involved in this prestigious annual event where the students would get a vast exposure working behind the scene for a major international event as well as enhance their knowledge on the current trends in global tourism industry. All the students involved in the program were from the Faculty of Hotel & Tourism Management and they were supervised by two Tourism Lecturers (Mohd Faisal Abdul Wahab and Zarifah Mohd Zain) PYS 2018 with the theme: Inspiring Tourism Leaders of Tomorrow was hosted by the Langkawi Development Authority (LADA) and the Alumni Association of UiTM Students' Representative Council (PIMPIN) in collaboration with the PATA Malaysia Chapter, Tourism Malaysia and Langkawi UNESCO Global Geopark. PYS 2018 (held on 12 September 2018) was conducted in conjunction with PTM 2018 (starting from 13-14 September 2018) and both events were held at Mahsuri International Exhibition Centre (MIEC), Pulau Langkawi.